Synthesis and Characterization of Hydroxyapatite Nanocrystalsvia Chemical Precipitation Technique: Synthesis and characterization of hydroxyapatite - Hossein Eslami; Mehran Solati-Hashjin; Mohammadreza Tahriri (Iranian Journal of Pharmaceutical Sciences, 2008)
In this study, hydroxyapatite (HA) nanocrystals have been synthesized via chemical precipitation technique. Diammonium hydrogen phosphate and calcium nitrate 4-hydrate were used as starting materials and sodium hydroxide solution was used as the agent for pH adjustment. The powder sample was evaluated by techniques such as scanning electron microscope, transmission electron microscope, Fourier transform infra-red spectroscopy, differential thermal analysis, thermal gravimetric analysis, X-ray diffraction, atomic absorption spectroscopy and EDTA titrationan alyses. According to the above-experimental results, it was found that hydroxyapatite nanocrystals can successfully be produced through wet precipitation method. The bulk Ca/Pmolar ratio of synthesized hydroxyapatite was determined as 1.71 that was higher than stoichiometric ratio (1.667) which is expected for a pure HAphase. Finally, transmission electron microscopic technique demonstrated that the crystallites of prepared powder were nanosized with a needle-like morphology.